Peningkatan Hasil Belajar Tema 9 Melalui Model Discovery Learning Pada Siswa Sekolah Dasar - Astuti, Dewi (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
The aim of this research is to improve student learning outcomes through the theme 8 discovery learning model for fourth grade students at SD Negeri Dukuhan Kerten Surakarta. This research is classroom action research (PTK). This research was carried out at SDN Dukuhan Kerten Surakarta with a total of 273 students. Data collection techniques in this research are observation, tests, and documentation. The data analysis technique used is interactive analysis, namely data reduction, data presentation, and conclusion. The results of the research show that the discovery learning model can improve learning outcomes for theme 9 "The Richness of My Country" in class IV students at SD Negeri Dukuhan Kerten for the 2022/2023 academic year. The increase occurred starting from cycle I at 38% and cycle II increased to 84.36%.